Literaturs Study: The Use Of The Qiroati Method For Early Children - Dwi Via Cahya Bulan; Emsya Salsabela; Hanisah Azzahrah; Husniawati Husniawati; Firman Robiansyah (Journal of Islamic Education for Early Childhood, 2023)
This purpose study aims to determine the use of the Qiroati method for reading the Qur'an which is applied to early childhood. At this golden age, moral and religious development needs to be given well, one of which is introducing and teaching children to read the Qur'an in an easy and fun way, so that children are able to recognize and learn it. The Qiroati method is a method of learning to read the Koran. research using the literature study method, through data collection techniques based on collecting literature sources. based on the results of the research literature it is known that the Qiroati method can be applied to early childhood because it is easy to understand and fun to use learning media that interests children. Thus, the use of the Qiroati method is known to be applicable to early childhood.